Research trends in human osteology: A content analysis of papers published in the American Journal of Physical Anthropology - Stojanowski, Christopher M.; Buikstra, Jane E. (American journal of physical anthropology, 2005)
This paper explores recent research trends in human osteology, based on articles published in the American Journal of Physical Anthropology (AJPA) during two 5‐year intervals: 1980–1984 and 1996–2000. Topical “visibility” is measured in terms of article counts; “impact” is estimated through citation indices. Our results indicate that human osteologists continue to publish a range of methodological, analytical, and descriptive research papers that address a broad array of subjects. Analytical articles are cited more frequently than descriptive articles and thus have higher impact, reflecting the discipline's continued commitment to problem‐oriented research. Differences in publication patterns exist between scholars during early and later stages of their careers. Articles published by students and Ph.D.s within 2 years of their doctoral degree are more frequently descriptive than analytical, when compared to people with longer career histories. Topics such as pathology, forensic anthropology, and biodistance modeling remain highly visible, while articles on the dentition have waned. An increase in functional research directed toward the postcranial skeleton is also reflected in our data. While continued visibility for morphological investigations is apparent, the impact of recently developed applications in bone chemistry and molecular anthropology is amply documented in our data, particularly during the more recent survey years. Am J Phys Anthropol 128:98‐109, 2005. © 2005 Wiley‐Liss, Inc.